Job Satisfaction as a Mediator Between Leadership, Organizational Learning, and Work Outcomes - Efrial, Annisa Syafira; Valentina, Debora Justice (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study investigates the influence of transformational leadership and organizational learning on employee performance, with job satisfaction examined as a mediating variable. The research aims to better understand how leadership behavior and learning culture interact to shape employee outcomes within multinational organizations. Data were collected through self-administered online Forms from 142 employees working in multinational companies across various sectors. The data were analyzed using Structural Equation Modeling (SEM) to test the direct and indirect relationships among the constructs. The results indicate that both transformational leadership and organizational learning have significant positive effects on job satisfaction and employee performance. However, job satisfaction does not mediate the relationship between transformational leadership and performance, while it serves as a mediator between organizational learning and performance. These findings highlight the nuanced interaction between leadership style, learning orientation, and employee outcomes. The study underscores the importance of cultivating a learning-oriented organizational culture that enhances employee satisfaction and drives superior performance. By fostering transformational leadership practices and continuous learning, multinational organizations can sustain long-term competitiveness and improve workforce engagement. This research contributes theoretical insights and practical implications for leadership development and organizational learning strategies in global business contexts.